Correlation between DAS-28 and Neopterin as a Biochemical Marker of Immune System Activation in Early Rheumatoid Arthritis - D'agostino, Liliana Elena (2013)
Objective: The objective of this study was to evaluate neopterin plasma concentrations in patients with early Rheumatoid Arthritis (RA) and correlate them with disease activity. Methods: This is a 28-month prospective study carried out on 65 individuals. There were 27 patients with early RA and 38 healthy volunteers as control group. Enzyme immunoassay was used to measure concentrations of neopterin and anti-cyclic citrullinated peptide (CCP) antibodies. Rheumatoid factor (RF) and C-reactive protein (CRP) were measured turbidimetrically, and antinuclear antibodies (ANA) were detected by immunofluorescence. Patients with early RA disease activity were divided into 4 groups according to DAS-28 criteria. Neopterin concentrations in RA patients were compared to conventional RA diagnostic serological markers. Results: Healthy volunteers had a mean neopterin concentration of 5.63 ^ 0.38 [1.36?9.93] nmol. L21. A statistically significant elevation of neopterin mean concentration was found on early RA patients: mean value of 8.92 ^ 0.93 [3.94?28.3] nmol. L21 ( p , 0.001). Pearson product moment correlation suggests a correlation between neopterin concentrations and DAS-28 (r ¼ 0.208, p ¼ 0.065). The analysis of the mean values grouped according with the DAS-28 criteria showed a correspondence between these means, with a Pearson correlation coefficient r ¼ 0.979, p ¼ 0.021. CRP concentrations also showed a similar trend. Anti-CCP antibodies and RF revealed a positive relationship with RA activity. Such a correlation was not found with ANA results. Conclusions: The elevation of plasma neopterin concentrations in early RA patients may indicate stimulation of immune response. Good correlation between neopterin concentrations and DAS-28 may facilitate assessing disease activity.